2015
DOI: 10.1108/imefm-03-2014-0029
|View full text |Cite
|
Sign up to set email alerts
|

Integration of waqf-Islamic microfinance model for poverty reduction

Abstract: Purpose-This paper aims to develop an integrated waqf-based Islamic microfinance (IsMF) for poverty reduction in Bangladesh. Microfinance institutions (MFIs) have been constrained by the high cost of funds, high interest rate charges and poor human resource quality of the recipients. Islamic MFIs have recently evolved with the hope of overcoming these financial, ethical and human capital deficiencies faced by the conventional financial institutions. Moreover, a good number of integrated models have been propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
120
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 6 publications
7
120
0
5
Order By: Relevance
“…Islamic microfinance, on the other hand, provides interestfree loan (qard hasan) or profit-loss sharing system based on Mudharabah (Haneef et al, 2015). In relation to that, Islamic microfinance institutes may have the great potential of reaching the bottom of pyramid due to its interest-free loans.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Islamic microfinance, on the other hand, provides interestfree loan (qard hasan) or profit-loss sharing system based on Mudharabah (Haneef et al, 2015). In relation to that, Islamic microfinance institutes may have the great potential of reaching the bottom of pyramid due to its interest-free loans.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Hassan (2014), such collective efforts to promote economic activities and regional development will affect both production and consumption of a community. However, as Haneef et al (2015) suggested, it is important to provide educational and training programmes to the borrowers so that the borrowers are equipped with necessary know-how to run their businesses or agricultural farms.…”
Section: Prospects and Challenges Of The Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In Turkey, waqf system has contributed significantly in providing employment other than those employed directly by the state. Recent studies on the potential of waqf have revealed that the system can significantly contribute to poverty alleviation by providing them opportunities to generate their income from favourable economic activities (Ali 2014;Haneef et al, 2013;Hassan, 2010;Shirazi, 2014;Zarka, 2007).…”
Section: The Economic Role Of Waqfmentioning
confidence: 99%
“…Prior researches provided evidences on the studies conducted on the acceptance of Islamic financial products such as Qardhul Hassan in the emerging markets such as Malaysia (Amin, Ghazali, & Supinah, 2010;Mansori, Kim, & http://dx.doi.org/10.15405/epsbs.2016.08.109 eISSN: 2357-1330 Selection and peer-review under responsibility of the Organizing Committee 776 Safari, 2015), Iran (Mojtahed & Hassanzadeh, 2009), Libya (Ali Khalifa & Bardai, 2013), Bangladesh (Haneef, Pramanik, Mohammed, Bin Amin, & Muhammad, 2015;IFSB, 2014;Khan, Hassan, & Shahid, 2007) and Indonesia (Febianto & Ashany, 2012;Yumna & Clarke, 2013). Moreover, in the developed countries, similar studies were conducted such as in Australia (Sain, Rahman, & Khanam, 2013) and UK (Warsame, 2009).…”
Section: Introductionmentioning
confidence: 99%